Potentially Inappropriate Medications in a Psychogeriatric Inpatient Ward: An Audit Based on Beers Criteria - Isabelle Moebs; Esther Abeln; Annalise Siefert; Yoram Barak (Neurology and Therapy, 2020)
Abstract Introduction Older adults are often prescribed a high number of medications. Overcoming inaction in health care is difficult but essential to deprescribing potentially inappropriate medications (PIMs). Curbing the use of PIMs is urgent in older adults suffering from psychiatric illness, as cognitive, emotional and psychosocial adversity makes them an especially vulnerable group. We aimed to audit PIM usage and deprescribing in an old-age psychiatry inpatient service of a university-affiliated public hospital. Methods The 2015 American Geriatrics Society (AGS) Beers Criteria were used in the present study. Computerized medical records were reviewed for all patients discharged from the Dunedin Public Hospital Inpatient Psychogeriatric Ward during the period January 2017 to December 2017. Results During the 1-year study period, 136 patients were discharged from our psychogeriatrics inpatient ward, including 87 women and 49 men, with a mean age of 75.4 ± 8.6 years (range: 59–95). The mean number of medications prescribed per patient at the time of admission was 7.7. At discharge, a mean of 8.9 medications were recorded. Analysis focused on 120 complete patient records. Of the 49 patients with 63 high-risk medications, 16 patients (prescribed 19 high-risk medications) had their high-risk medication stopped, 23 patients (prescribed 24 high-risk medications) had high-risk medications started and 10 (prescribed 20 high-risk medications) had no change to high-risk medications between admission and discharge. In 56 of 120 patients (47%), benzodiazepines (BZDs) were started, stopped or unchanged. Conclusion Older adults suffering from severe psychiatric disorders are frequently prescribed PIMs. However, clinical decision-making for this vulnerable population needs to take into account safety as reflected by the Beers Criteria, but also the complexity of managing psychogeriatric problems.